1998
DOI: 10.1021/ma9717294
|View full text |Cite
|
Sign up to set email alerts
|

Application of “Transfer-Free” Suzuki Coupling Protocols toward the Synthesis of “Unambiguously Linear” Poly(p-phenylenes)

Abstract: Soluble derivatives of poly(p-phenylene) of high molecular weight were synthesized via Suzuki coupling reactions catalyzed by palladium(0) precursors in the presence of either triphenylphosphine (TPP) or tri(o-tolyl)phosphine (TOTP). Syntheses involving the former ligand resulted in the formation of polymers in which the incorporation of phosphine was clearly observable by 31 P NMR. However, polymers formed utilizing the latter ligand in a hydrophobic solvent such as CH2Cl2 exhibited no signals in the 31 P NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 100 publications
1
64
0
Order By: Relevance
“…Optimization of the crosscoupling conditions demonstrated that the use of bulky phosphine ligands such as tri(o-tolyl)phosphine, resulted in higher molecular weights than for less bulky ligands like triphenylphosphine, most likely due to the suppression of ligand transfer reactions that can occur to the growing polymer chain from less bulky ligands. [89] The use of microwave heating and sealed reaction tubes facilitated the reaction, enabling superheating of the solvent (chlorobenzene) and reducing reaction times from days to minutes. [90] Similar findings have been reported for the use of microwave heating in other polymerizations.…”
Section: Polymerization Of Thienothiophene Polymersmentioning
confidence: 99%
“…Optimization of the crosscoupling conditions demonstrated that the use of bulky phosphine ligands such as tri(o-tolyl)phosphine, resulted in higher molecular weights than for less bulky ligands like triphenylphosphine, most likely due to the suppression of ligand transfer reactions that can occur to the growing polymer chain from less bulky ligands. [89] The use of microwave heating and sealed reaction tubes facilitated the reaction, enabling superheating of the solvent (chlorobenzene) and reducing reaction times from days to minutes. [90] Similar findings have been reported for the use of microwave heating in other polymerizations.…”
Section: Polymerization Of Thienothiophene Polymersmentioning
confidence: 99%
“…A way of overcoming long reaction times is the use of microwave-assisted coupling reactions. [33][34][35] Besides, aryl-aryl interchange reactions between palladiumand phosphine-bound aryls [36][37][38][39][40][41] can lead to an unwanted incorporation of phosphines into the polymer chain. Last but not least, Pd(PPh 3 ) 4 is air-sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding SPC with diiodo monomers there are two reports in the literature. Based on earlier work by Percec 4) , Weder oligomerized diiodo benzene and a saturated bifunctional boron compound 5) and Novak polymerized a 4,49-diiodobiphenyl with a 4,49-biphenyl diboronic acid ester to give the corresponding high molecular weight poly(para-phenylene) 6) . Novak also found using Pd 2 (dba) 3 with P(o-tolyl) 3 as co-ligand that in this reaction no ligand derived phosphorus incorporation into the backbone takes place.…”
mentioning
confidence: 99%